2019
DOI: 10.1038/s41598-019-47339-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the longitudinal dynamics of herd BVD antibody test results using model-based clustering

Abstract: Determining the Bovine Viral Diarrhoea (BVD) infection status of cattle herds is a challenge for control and eradication schemes. Given the changing dynamics of BVD  virus (BVDV) antibody responses in cattle, classifying herds based on longitudinal changes in the results of BVDV antibody tests could offer a novel, complementary approach to categorising herds that is less likely than the present system to result in a herd’s status changing from year to year, as it is more likely to capture the true exposure dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The multivariate mixture of generalized mixed effects clustering model 32 incorporates Bayesian inference to explore heterogeneity in the longitudinal brain data. We applied this model on brain volume/thickness but it has already been used in other applications 31,[33][34][35][36][37][38][39][40][41][42] . The Bayesian approach allowed the implementation of a complex hierarchical model for each cluster, where probabilistic mixture modeling (number of clusters) is combined with mixed effect modeling (number of brain regions) in one model definition.…”
Section: Longitudinal Clustering Analysismentioning
confidence: 99%
“…The multivariate mixture of generalized mixed effects clustering model 32 incorporates Bayesian inference to explore heterogeneity in the longitudinal brain data. We applied this model on brain volume/thickness but it has already been used in other applications 31,[33][34][35][36][37][38][39][40][41][42] . The Bayesian approach allowed the implementation of a complex hierarchical model for each cluster, where probabilistic mixture modeling (number of clusters) is combined with mixed effect modeling (number of brain regions) in one model definition.…”
Section: Longitudinal Clustering Analysismentioning
confidence: 99%
“…By removing the weight of the starting point of the trajectory (centering) we were able to focus on the shape of the trajectories and capture the variation in growth that happens in the first 24 months of life. A similar normalizing approach has been used to identify patterns of crime over time and changes in antibody levels between animals of different farms 16 , 17 . Researchers showed that when correcting by the mean value of the farm the scale of the antibody effect and the variability between farms were removed 17 .…”
Section: Discussionmentioning
confidence: 99%
“…A similar normalizing approach has been used to identify patterns of crime over time and changes in antibody levels between animals of different farms 16,17 . Researchers showed that when correcting by the mean value of the farm the scale of the antibody effect and the variability between farms were removed 17 . Similar to the change in growth we captured in the patterns in our study, clustering by shape not only provided information on the direction of change, but also other complex nonlinear patterns which may www.nature.com/scientificreports/ be influenced by changes in time.…”
Section: Discussionmentioning
confidence: 99%
“…In Scotland and Ireland, analyzes of BVD eradication schemes have focused on costs and benefits ( 46 , 47 ), modeling the optimal testing methods for achieving eradication ( 48 ) and epidemiological analyzes of the schemes ( 3 , 4 , 49 ). Reviews have been carried out on the voluntary phase of the eradication scheme in Ireland ( 50 ) and more recent analyzes of the design, progress, and challenges toward BVD eradication ( 51 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%